Representation of Expressions of Congratulations via WhatsApp Stickers from the Viewpoint of the Sender and Receiver of the Message - Sarro, Abd. Halim; Unde, Alimuddin; Mau, Muliadi (State Islamic Institute of Bone, Indonesia, 2025)
Communication of condolences in the digital era has experienced significant changes with the presence of WhatsApp stickers as a nonverbal medium. This research aims to explore how stickers are used to convey condolences, both from the perspective of the sender and recipient of the message. Using a qualitative approach, in-depth interviews were conducted with 20 active WhatsApp users who had used or received stickers in the context of condolences. The research results show that stickers are chosen by senders to convey empathy visually, overcome language barriers, and maintain a polite impression, especially in relationships that are not too close. Symbols such as flowers, candles, or neutral colors are common choices because they are considered universal. However, message recipients had mixed responses. Most appreciated the sender's good intentions, but some felt that the stickers were less personal and did not convey enough depth of emotion in a situation of intense grief. The potential for miscommunication is also found if the context and sticker symbols are inappropriate or difficult to understand. This study highlights the importance of sensitivity in using WhatsApp stickers as a medium for emotional communication as well as the need for digital literacy to support more empathetic and effective visual communication.